High-power short-duration versus low-power long-duration ablation guided by the ablation index. (1st January 2023) - Sousa, Pedro A.; Puga, Luís; Barra, Sérgio; Adão, Luís; Primo, João; Khoueiry, Ziad; Lebreiro, Ana; Fonseca, Paulo; Pereira, Mariana; Lagrange, Philippe; d'Avila, Andre; Oliveiros, Bárbara; et al.
Abstract: Aims: To compare the two different ablation strategies, both guided by the Ablation Index (AI), in the setting of atrial fibrillation (AF) ablation: high-power short-duration (HPSD) ablation using 40 W on the posterior wall and 50 W elsewhere versus low-power long-duration (LPLD) using 25 W posteriorly and 35 W elsewhere. Methods: Prospective, multicenter nonrandomized, noninferiority study of consecutive patients referred for paroxysmal AF ablation from January 2018 to July 2019. Ablation was guided by the AI (≥500 for anterior segments, ≥450 for the roof and inferior segments and 400 posteriorly) and an interlesion distance (ILD) ≤ 6 mm. Patients were separated into two groups: HPSD vs LPLD. Acute reconnection (after adenosine trial) and 2-year outcomes were assessed. Results: 160 patients (61% males, median age of 62 [IQR 51–69] years), fulfilled the study inclusion criteria – 80 patients (316 pulmonary veins [PV]) in the HPSD group and 80 patients (314 PV) in the LPLD. The probability of acute PV reconnection was similar between both groups: 2.2% in HPSD, 95%CI 0.6% to 3.8% vs. 3.4% in LPLD, 95%CI 1.4% to 5.4%; p  < 0.001 for noninferiority. Median PV ablation time (20 min vs 30 min, p  < 0.01) and procedure duration (80 min vs 100 min, p < 0.001) were shorter in the HPSD group. After a median follow-up of 26 months, arrhythmia recurrence was similar between groups (17.5% in HPSD group vs. 18.8% in LPLD group, p  = 0.79). Conclusions: In paroxysmal AF patients treated with the Ablation Index, a HPSD strategy is noninferior to the more standard LPLD ablation, while allowing for quicker procedures with shorter ablation times. Highlights: This is the largest prospective study in paroxysmal AF ablation comparing acute PV reconnection between HPSD and LPLD, guided by the same AI value. The use of a HPSD strategy was not inferior to the LPLD strategy with similar acute PV reconnection, while allowing for quicker procedures and shorter RF time. It provides the longest-term comparison of two-AI guided PVI strategies demonstrating that at 26 months of follow-up, HPSD was as effective as a LPLD strategy.